Investigating the Role of Cigarette Smoke and Alcohol in Oesophageal Squamous Cell Carcinoma - Gamieldien, Raabie'ah (Department of Integrative Biomedical Sciences (IBMS), 2023)
The World Health Organisation (WHO) has estimated cancer to be one of the leading causes of death to people under the age of 70. Every year there are about 18.1 million new cancer cases worldwide; oesophageal cancer (OC) ranks seventh out of all incidence cases and sixth in mortality. OC has a poor 5-year overall survival rate of about a 15% (Arnal et al., 2015). This occurs as OC is largely asymptomatic and patients often seek medical assistance at a late stage of their cancer. This late diagnosis and a lack of efficient treatment has rendered OC a serious world health problem. Oesophageal Squamous Cell Carcinoma (OSCC) is the more common subtype of and accounts for about 90% of incident oesophageal cancers every year (Abnet et al., 2018) with the majority of OSCC cases occur in developing countries. The objective of this study was to investigate cigarette smoking and alcohol consumption as they have widely been reported as risk factors for OSCC. The project explored the impact of cigarette smoke condensate (CSC) treatment and EtOH on the expression of genes in cultured oesophageal cancer cells. Prior to treating the cells for expression analysis, cytotoxicity experiments were conducted to determine treatment conditions of CSC and EtOH which were sub-lethal, for the cell types and timeframes investigated. It was found that concentrations of 40 µg/ml CSC and 50 mM EtOH did not cause cell death for the time period of three days. Furthermore, we also showed that cell viability was maintained up to 10 days of treatment. RNA-sequencing then revealed a wide variety of genes that were differentially expressed in the OSCC cells treated with these selected concentrations of CSC and EtOH. One gene found to be differentially expressed in two RNA-Seq analyses was confirmed to be upregulated by RT-qPCR. Seven genes, AHRR, ALDH3A1, CYP1A1, CYP1B1, GSTM3, GSTM4 and UGT1 A6, involved in xenobiotic metabolism and a number of other metabolic pathways were also altered in response to CSC and EtOH treatment. However, these genes' involvement require further confirmation by RT-qPCR. This result of this study confirms that we have designed a reliable experimental system to investigate the role of EtOH and CSC in the development of OSCC. These results gave us a deeper insight into the genes and pathways affected by CSC and EtOH which may contribute to OSCC. Additionally, the cytotoxicity data can be use for future experimental work and the RNA-seq data can be used for further investigation into the development of OSCC.